Strategi Negosiasi Dalam Pemilihan Umum: Analisis Game Theory Terhadap Koalisi Politik Di Indonesia - Vellayati Hajad; Ikhsan Ikhsan; Herizal Herizal; Zuhrizal Fadhly; Sri Wahyu Handayani (Jurnal Agregasi, 2026)
This study examines negotiation strategies in political coalition formation during Indonesian elections using Game Theory analysis. The complexity of Indonesia's multi-party system often results in unstable coalition governments, highlighting the importance of understanding inter-party negotiation dynamics. The research aims to identify strategic patterns in political negotiations and optimize coalition formation strategies. The methodology includes analysis of historical election data, interviews with political figures, and application of Game Theory models such as Nash Equilibrium and coalition bargaining. The results demonstrate that the Game Theory approach can predict and explain party behavior in coalition formation with high accuracy. These findings provide new insights for optimizing political strategies in Indonesia and contribute to the development of coalition formation theory in multi-party systems.